Determinación de los métodos de control de ácaros en el cultivo de rosas (Rosae sp.) variedad explorer en el Cantón Espejo, Provincia del Carchi - Pilacuan Ortiz, Angélica Jhomayra (2019)
SUMMARY The present investigation was carried out in five floricultural plants of the Cantón Espejo, with the purpose of determining the control of mites in the cultivation of roses. The information was collected through surveys, which consisted of thirteen questions. The results obtained indicate that 100% of the flower women surveyed in Cantón Espejo have problems due to the attack of mites in the explorer variety, causing damages such as chlorosis, yellowish or brown points, diminution of the production and quality of the flower; the floriculturists state that the environmental factor causes the greatest incidence of this pest, such as high temperatures and high levels of nitrogen fertilization; 83% of the floriculturists carry out the chemical control, for this, 50% of floriculturalists use Acaristop in doses of 1 to 1.5cc, 17% use aji garlic extract in a dose of 2cc plus potassium soap in a dose of 1, 5cc and Peroxiplus in 2cc doses and 16% of floriculturals use Kendo in 2cc doses; In the same way the floriculturists show that by making chemical preventions and applications they manage to lower the incidence of mites so as not to lower their production and have an excellent export product. In conclusion, floriculture companies with the purpose of reducing the presence of mites in the rose garden perform preventive controls such as: foliar washing with water and potassium soap, perform sanitary pruning, frequent monitoring of the crop, water sprays, cultural work, maintain a adequate ventilation in the greenhouse, fertilization plans according to the needs of the plants and keep the rose bush moist, that is to say field capacity and ventilate the greenhouse at high temperatures to avoid the incidence of the mite, all this considering the quality requirements of the rose of international markets and the great investment that farming implies. Keywords: roses, mites, controls, factors, damage.